A phenomenological approach to virtual reality in psychiatry education - Pedersen, Kamilla; Musaeus, Peter (Frontiers in Virtual Reality, 2023)
Virtual Reality has emerged as a valuable tool in medical education, primarily for teaching basic sciences and procedural skills. However, its potential in clinical psychiatry, particularly in comprehending the subjective experiences of individuals with mental illness, remains largely untapped. This paper aims to address this gap by proposing a phenomenological-driven approach to the design of virtual reality in psychiatry education. Insights into psychopathology, which involves the systematic study of abnormal experiences as well as self-awareness on behalf of the clinician, demands training. The clinician must develop sensitivity, observational skills, and an understanding of patients’ subjective experiences. While integrating the subjective perspective and promoting emotional self-awareness in psychiatry education have been recommended, further research is necessary to effectively harness virtual reality for this purpose. Drawing from the convergence of virtual reality, phenomenological approaches to grasping subjectivity and psychopathology, this paper aims to advance teachings in psychopathology. It underscores the importance of integrating biomedical knowledge with the lived experiences of psychiatric patients to offer learners a comprehensive understanding of clinical psychiatry. This approach is deeply rooted in the theories of three influential figures: Karl Jaspers, a German psychiatrist and philosopher, who emphasized the role of phenomenology in clinical psychiatry; Ludwig Binswanger, a Swiss psychiatrist and psychotherapist, known for his work on existential analysis; and Medard Boss, a Swiss psychiatrist and psychoanalyst, who introduced Daseinsanalysis, focusing on the individual’s existence in the world. To facilitate learning in acute psychiatry, a virtual reality scenario was developed. This scenario offers two perspectives: one from the patient’s viewpoint, simulating a severe psychotic incident, and the other from the perspective of junior doctors, exposing them to the challenges of communication, decision-making, and stress in a clinical setting. This paper argues that these phenomenological approaches are valuable in helping inform the didactical considerations in the design of the virtual reality scenario, enhancing the learning experience in psychiatry education. It highlights the potential of virtual reality to deepen understanding in the teaching of clinical psychiatry and provides practical insights into its application in an educational context.